(untitled) (Tempo e Argumento, 2021)
In this article, we will initially present the concept of degeneration developed by Benedict-Augustin Morel, Valentin Magnan and Emil Kraepelin, as well as its repercussions on Brazilian psychiatry in the early years of the 20th century. Based on these assumptions, we will discuss the life trajectory of people considered to have mental disorders and psychiatric knowledge at the Hospital for Nervous and Mental Diseases of Recife, through the analysis of some medical records from the 1920s with patients diagnosed with the Delusional Episode Degeneration. The support of this research is in the work developed in the collection of the Hospital Ulysses Pernambucano, in which the recovery of documentation, cataloging and the edition of an inventory of all books between the years 1926 to 1970 was carried out, in a total of 1013 volumes, each with fifty records. The analysis of these important sources, together with the theoretical contribution, allowed the elaboration of this article Keywords: Hospital; psychiatry; degenerate; eugenics.